Effect of face mask on pulmonary artery pressure during echocardiography in children and adolescents - Alireza Ahmadi; Mohammad Reza Sabri; Zohreh Sadat Navabi (The Korean Pediatric Society, 2024)
Background Face masks have become an important tool for preventing the spread of respiratory diseases. However, we hypothesized that face masks with reduced nasal airﬂow may alter pulmonary artery systolic pressure (PASP). Purpose This study aimed to evaluate the eﬀect of face masks on PASP in children and adolescents. Methods This case-control study was conducted between March 2021 and April 2022 at the Pediatric Cardiovascular Research Center in Isfahan, Iran. Using a convenience sampling method, a total of 120 children and adolescents, boys and girls aged 3-18 years, were allocated into 2 groups of 60 each (case group with congenital heart disease (CHD), control group of healthy subjects). For each patient in the case and control groups, echocardiography (ECHO), heart rate (HR), and blood oxygen saturation (SpO2) were performed and measured twice-once with a surgical mask and once without a surgical mask-by a pediatric cardiologist at 10-min intervals. Results A total of 110 participants were analyzed. The mean patient age was 9.58±3.40 years versus 10.20±4.15 years in the case (n=50) and control (n=60) groups, respectively. Approximately 76.0% (n=38) of the participants in the case group versus 60.0% of those in the control group were male. In the case and control groups, there was a statistically significant reduction in the mean changes in tricuspid regurgitation (P=0.001), pulmonary regurgitation (P=0.002), and PASP (P=0.001) after face mask removal. Although this study showed a reduction in pulmonary arterial pressure after face mask removal in patients with CHD and healthy subjects, no significant changes in HR (P=0.535) or SpO2 (P=0.741) were observed in either group. Conclusion Wearing a face mask increased PASP in healthy children and adolescents with CHD; however, the SPO2 and HR remained unchanged. Therefore, mask removal during ECHO is recommended.